Analisis Kondisi Keuangan Pemerintah Daerah Berdasarkan Peraturan Menteri dalam Negeri (Permendagri) Nomor 19 Tahun 2020 - Siti Anggraeni; Andy Lasmana; Saepul Anwar (Universitas Dian Nuswantoro, 2024)
This study aims to identify the differences in regional financial conditions over the period of 2020-2022 in provinces with special autonomy, representing each cluster in the IPKD for the fiscal year 2022. The author evaluates financial condition indicators based on the Regulation of the Minister of Home Affairs Number 19 of 2020 in regions classified as high, medium, and low clusters, represented by Jakarta, Aceh, and Yogyakarta respectively. The results of the study conclude that Jakarta demonstrates strong and stable financial performance in almost all indicators. As a region in the high cluster and the capital city, Jakarta's good financial condition should serve as a reflection and example for other regions in managing regional finances. Aceh faces significant challenges in its financial management. Despite improvements in financial independence and flexibility, operational and short-term solvency show significant fluctuations. Meanwhile, Yogyakarta shows improvements in financial independence and flexibility, although it still faces challenges in operational solvency.